High-thermal-conductivity long-carbon-chain nylon composite material and continuous synthesis method thereof

By using graphene oxide/boron nitride nanosheet composites in long-carbon chain nylon composites and adopting continuous production line equipment polymerization process, the problems of poor compatibility and low production efficiency of high-thermal conductivity long-carbon chain nylon composites are solved, and the effects of high thermal conductivity and stable product quality are achieved.

CN119613712APending Publication Date: 2025-03-14SHANDONG DONGCHEN ENG PLASTIC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411868374.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing high thermal conductivity long carbon chain nylon composite materials have problems such as poor compatibility and inability to produce continuously, resulting in low production efficiency and unstable product quality.

Method used

Graphene oxide/boron nitride nanosheet composite material is prepared by peeling hexagonal boron nitride with graphite oxide, which is uniformly dispersed in the long carbon chain nylon salt solution, and polymerized through continuous production line equipment to form a high thermal conductivity long carbon chain nylon composite material.

Benefits of technology

The excellent thermal conductivity and stable product quality of high thermal conductivity and long carbon chain nylon composite materials have been achieved, which improves production efficiency and overcomes the problem of poor compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613712A_ABST
    Figure CN119613712A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity long-carbon-chain nylon composite material and a continuous synthesis method thereof. The composite material is prepared from the following components in parts by mass: 70 to 95 parts of long-carbon-chain nylon salt, 5 to 30 parts of spherical GO / BNNSs, 0.01 to 0.05 part of catalyst and 0.01 to 0.1 part of antioxidant, the spherical GO / BNNSs are compounded by spherical GO / BNNSs stripped for 1-3 hours and spherical GO / BNNSs stripped for 5-7 hours according to the mass ratio of 1: (1-2); all the components are added into a continuous production line salt forming tank, and the high-thermal-conductivity long-carbon-chain nylon composite material is obtained through salt forming, polymerization, grain-sized dicing and drying. The spherical GO / BNNSs disclosed by the invention are simple in preparation process, and the spherical GO / BNNSs stripped for different time are compounded, so that a heat-conducting path can be quickly established; according to the continuous synthesis method, the synthesis process can be accurately controlled, the production efficiency is improved, and the obtained high-thermal-conductivity long-carbon-chain nylon composite material is stable in quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering plastics, and in particular relates to a high-thermal-conductivity long-carbon-chain nylon composite material and a continuous synthesis method thereof. Background Art

[0002] As a new type of functional material, high thermal conductivity long carbon chain nylon has broad application prospects in the fields of automobiles, communications, electronics and electrical engineering. It can be used to manufacture high-performance heat dissipation components, effectively improving the stability and service life of equipment. For example, it can be used as a battery pack shell to assist in the thermal management of the battery and ensure battery safety and performance. The common preparation method is to add fillers with high thermal conductivity, such as boron nitride and graphene, to the long carbon chain nylon substrate through modification means, but the compatibility between graphene and boron nitride and long carbon chain nylon is poor. Although researchers have improved the compatibility by adding auxiliary agents such as coupling agents, it is still difficult to compound the two evenly by simple blending modification.

[0003] CN110734642A discloses an insulating high-strength nanocomposite material and a preparation method thereof, wherein hydroxylated boron nitride is added to caprolactam, and a grafting reaction occurs between the hydroxylated boron nitride and the caprolactam while the caprolactam is hydrolyzed and ring-opened polymerized. This method of preparing a boron nitride-nylon 6 composite material by polymerization can effectively solve the above-mentioned problems, and make the high-filling boron nitride uniformly dispersed in the matrix to reduce the interface thermal resistance. In the above method, the interaction between the hydroxyl group of the boron nitride and the amino group and carboxyl group of the nylon is relatively low, and there are still limitations in applying it to the polymerization of long carbon chain nylon.

[0004] CN118955958A discloses a nylon material with thermal conductivity and a preparation method thereof. A modified thermal conductive filler is obtained by modifying graphene and boron nitride, and then added to the modified nylon organic solvent. Compared with adding unmodified thermal conductive fillers composed of graphene and boron nitride, the thermal conductive filler can significantly improve the thermal conductivity of the nylon material. However, the preparation process is complicated, and both the thermal conductive filler and the nylon resin need to be modified, and the thermal conductivity and impact resistance are limited.

[0005] At present, the polymerization process of long carbon chain nylon is usually intermittent polymerization, which has the disadvantages of low production efficiency, inability to fully utilize the reactor, unstable product quality, and inability to carry out large-scale production. Therefore, the development of a high thermal conductivity long carbon chain nylon composite material with simple preparation process and continuous production is of great significance to promote the advancement of electronic and electrical cooling system technology. Summary of the invention

[0006] In view of the problems that high thermal conductivity long carbon chain nylon composite materials in the prior art generally have poor compatibility and cannot be continuously produced, the present invention provides a high thermal conductivity long carbon chain nylon composite material and a continuous synthesis method thereof, wherein a graphene oxide (GO) / boron nitride nanosheet (BNNSs) aqueous solution obtained by exfoliating hexagonal boron nitride from graphite oxide is spray-dried to prepare a hydrophilic spherical graphene oxide / boron nitride nanosheet composite material (GO / BNNSs), which is uniformly dispersed in a long carbon chain nylon salt solution, and polymerized by a continuous production line equipment to obtain a high thermal conductivity long carbon chain nylon composite material. During the polymerization process, the hydroxyl and carboxyl groups on GO / BNNSs can be grafted with the amine and carboxyl groups on the long carbon chain nylon to form a strong interaction, which promotes the close combination of GO / BNNSs and the long carbon chain nylon, forming a stable heat conduction path in the nylon matrix, and achieving a superior heat conduction effect. Secondly, a continuous production line is used to form an automated continuous polymerization process, which improves production efficiency, can achieve precise control of the production process, and has stable product quality.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A high thermal conductivity long carbon chain nylon composite material, comprising the following components by mass:

[0009]

[0010] Furthermore, the preparation method of the spherical GO / BNNSs is as follows: hydrophilic graphite oxide and hexagonal boron nitride are added to water and peeled for 1 to 7 hours to obtain a GO / BNNSs dispersion, and then spray-dried to obtain spherical GO / BNNSs.

[0011] Furthermore, the spherical GO / BNNSs are prepared by compounding spherical GO / BNNSs peeled for 1 to 3 hours and 5 to 7 hours in a mass ratio of 1:1 to 2.

[0012] Furthermore, the mass ratio of the hydrophilic graphite oxide, hexagonal boron nitride and water is 5:1 to 3:100; and the stripping rotation speed is 1800 to 2200 rpm.

[0013] Furthermore, the spray drying temperature is 170-190° C., and the time is 5-15 min.

[0014] Furthermore, the long carbon chain nylon salt is prepared from a dibasic acid, a diamine and water; the molar ratio of the dibasic acid, the diamine and water is 1:0.9 to 1.1:25; the dibasic acid is one or more of adipic acid, sebacic acid, undecanedioic acid and dodecanedioic acid; the diamine is decanediamine or dodecanediamine.

[0015] Furthermore, the catalyst is one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, sodium phosphite, and sodium hypophosphite.

[0016] Furthermore, the antioxidant is one or more of transition metal salts, hindered amines, hindered phenols, phosphites and thiols.

[0017] The present invention also provides a continuous synthesis method of a high thermal conductivity long carbon chain nylon composite material: long carbon chain nylon salt, spherical GO / BNNSs, catalyst, and antioxidant are added to a salt-forming tank of a continuous production line according to the above-mentioned mass fractions, and then the high thermal conductivity long carbon chain nylon composite material is obtained through salt formation, polymerization, pelletizing, and drying.

[0018] The above continuous synthesis method has the following specific steps:

[0019] (1) Salt formation: According to the above formula, dibasic acid, diamine and pure water are added to the salt formation tank in sequence to obtain long carbon chain nylon salt, and the salt formation temperature is set to 70-80°C. When the pH value of the sample test is 8.5-9.5, spherical GO / BNNSs, catalyst and antioxidant are added while stirring at a stirring frequency of 20-30 Hz to obtain a mixed solution;

[0020] (2) Polymerization: The mixed solution obtained in step (1) is filtered through a filter with a mesh size of 180-220 mesh to remove impurities through potential difference and pressure difference, and then transported to a refined salt storage tank, and then pumped into a reaction preheater by a reactor supply pump. After preliminary heating in the reaction preheater at 160-200° C., the mixed solution is pumped into a reactor by a gear pump, and the temperature is raised to 200-210° C. and the pressure is raised to 1-2 MPa for dehydration for 1-3 hours, so that the concentration of the mixed solution is 90-95%; The mixed solution is pumped into the flash evaporator by a flash evaporator supply pump and dehydrated for 2 to 4 hours at 260 to 280° C. and normal pressure to obtain a nylon oligomer; the mixed solution is pumped into the prepolymerizer by a potential difference and dehydrated for 2 to 4 hours at 250 to 260° C., and then pumped into the postpolymerizer by a postpolymerizer supply pump and dehydrated and polymerized for 1 to 3 hours at 250 to 260° C. to obtain a polymer in a molten state; the mixed solution is pumped into the casting head by a melt metering pump for extrusion distribution to form a high thermal conductivity long carbon chain nylon composite material in the form of a strand belt;

[0021] (3) pelletizing: cooling the high thermal conductivity long carbon chain nylon composite material in the form of a strand bundle obtained in step (2) with deoxygenated water at 23 to 27° C. and then pelletizing to obtain high thermal conductivity long carbon chain nylon composite material particles;

[0022] (4) Drying: The high thermal conductivity long carbon chain nylon composite material particles obtained in step (3) are placed in a drying device and dried at 90 to 110° C. for 3 to 6 hours to obtain a high thermal conductivity long carbon chain nylon composite material.

[0023] Preparation mechanism: The GO / BNNSs exfoliation system is a green and environmentally friendly aqueous solution. During the exfoliation process, the hydrophilic graphene oxide is first exfoliated by shear force in the direction perpendicular to the sheet and parallel to the sheet to obtain small-sized GO flake materials. Then GO is intercalated into the interlayer of blocky hexagonal boron nitride. GO and BNNSs are tightly bound by π-π bonds to form a dense GO / BNNSs composite material. Among them, graphene oxide has excellent hydrophilicity, and water molecules will attack BN during the exfoliation process. The defects of NSs are then grafted with hydroxyl functional groups to obtain hydrophilic spherical GO / BNNSs, which are rich in hydroxyl and carboxyl groups on the surface and can be evenly dispersed in aqueous solution, which is conducive to the uniform grafting of hydroxyl and carboxyl groups of spherical GO / BNNSs with carboxyl and amine groups on nylon chains during the polymerization process. Spherical GO / BNNSs have a high theoretical stacking density, which can increase the contact points between fillers and nylon salts, overcome the poor compatibility between graphene and boron nitride and long carbon chain nylon, and enhance the thermal conductivity of the material. Secondly, spherical GO / BNNSs of different sizes are compounded, and small-sized balls will fill the gaps of large-sized balls, quickly establish a thermal conductivity path, and are conducive to the formation of high thermal conductivity long carbon chain nylon composite materials.

[0024] Beneficial effects:

[0025] (1) The present invention prepares hydrophilic spherical GO / BNNSs by exfoliating hexagonal boron nitride with hydrophilic graphite oxide. The process does not add other surfactants, compatibilizers and other additives to avoid affecting the material properties. The preparation process is simple, which can effectively improve production efficiency and save production costs.

[0026] (2) Both GO and BNNSs have high thermal conductivity. The lamellar structure of BNNSs is much smaller than that of GO. Through high-speed exfoliation, the gaps between GO lamellars can be filled to prepare dense thermal conductive fillers. Spherical GO / BNNSs have a high theoretical stacking density, which can increase the contact points between the filler and nylon salt. Secondly, the spherical GO / BNNSs exfoliated at different times are compounded. The small-sized spheres will fill the gaps between the large-sized spheres and quickly establish a thermal conductive path, so that the prepared composite material has good thermal conductivity and excellent mechanical properties.

[0027] (3) The present invention is based on the formula of high thermal conductivity long carbon chain nylon composite material, and adopts a continuous production line to form an automated continuous polymerization process to obtain high thermal conductivity long carbon chain nylon composite material. The automated continuous polymerization process can effectively improve production efficiency, realize precise control of the production process, reduce batch differences, and ensure stable product quality. It can be applied to the large-scale production of high thermal conductivity long carbon chain nylon composite materials and has significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1SEM images of spherical GO / BNNSs obtained at different peeling times; A is the SEM image of spherical GO / BNNSs peeled for 2 h; B is the SEM image of spherical GO / BNNSs peeled for 6 h;

[0029] Figure 2 This is a continuous synthesis process diagram of high thermal conductivity long carbon chain nylon composite materials;

[0030] Figure 3 Infrared thermal imaging images of high thermal conductivity nylon composites containing GO / BNNSs of different shapes. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be specifically described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] (1) Source of experimental materials

[0033] The raw materials used in the examples and comparative examples all use the same commercially available products from the following sources:

[0034] Dodecanedioic acid: Shanghai Cathay Biotechnology Co., Ltd.; decanediamine: Shanghai Gaoming Chemical Co., Ltd.; catalyst: sodium hypophosphite, Jiangyin Yuanxin Chemical Co., Ltd.; antioxidant: copper salt antioxidant, Dongguan Tailong New Materials Technology Co., Ltd.; hexagonal boron nitride: Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.; graphite oxide: Zhongke Yueda (Shanghai) Materials Technology Co., Ltd.

[0035] (2) Preparation of experimental materials

[0036] a: Preparation of spherical GO / BNNSs: Graphite oxide and hexagonal boron nitride were added to 100 ml of water in a mass ratio of 5:1, and exfoliation was carried out in a high-speed homogenizer at a speed of 2000 rpm to obtain GO / BNNSs dispersions with exfoliation times of 2h, 4h, and 6h, respectively; the GO / BNNSs dispersions with different exfoliation times were dried in a 180°C spray dryer for 10 min to obtain spherical GO / BNNSs with exfoliation times of 2h, 4h, and 6h, respectively.

[0037] SEM images of spherical GO / BNNSs obtained at different peeling times are shown in Figure 2. Figure 1As shown, A is the SEM image of spherical GO / BNNSs peeled for 2 h, and B is the SEM image of spherical GO / BNNSs peeled for 6 h. It can be seen that with the extension of the peeling time, the size of the spherical GO / BNNSs becomes smaller.

[0038] b: Preparation of flaky GO / BNNSs: Graphite oxide and hexagonal boron nitride were mixed in a mass ratio of 5:1, added to 100 ml of water, and peeled in a high-speed homogenizer at a speed of 2000 rpm for 6 h to obtain a GO / BNNSs dispersion. The dispersion was directly centrifuged at 4000 rpm for 30 min, and then dried at 100°C for 4 h to obtain flaky GO / BNNSs.

[0039] c: Preparation of spherical GO: Graphite oxide was added to 100 ml of water and exfoliated in a high-speed homogenizer at a rotation speed of 2000 rpm for 6 hours to obtain a GO dispersion; the GO dispersion was dried in a spray dryer at 180°C for 10 minutes to prepare spherical GO.

[0040] d: Spherical BNNSs: Hexagonal boron nitride was added to 100 ml of water and exfoliated in a high-speed homogenizer at a rotation speed of 2000 rpm for 6 hours to obtain a BNNSs dispersion; the BNNSs dispersion was dried in a spray dryer at 180°C for 10 minutes to obtain spherical BNNSs.

[0041] Example 1

[0042] A continuous production method of a long carbon chain nylon composite material, the specific steps are as follows:

[0043] (1) Salt formation: The measured dodecanedioic acid, decanediamine and pure water were added to the salt formation tank in a molar ratio of 1:1:25 to prepare 90 parts of long carbon chain nylon salt. The salt formation temperature was set to 75°C. After reaching the reaction end point, the salt solution was sampled to test the pH value. When the pH value was 9, 10 parts of spherical GO / BNNSs stripped for 2 h, 0.01 parts of sodium hypophosphite and 0.02 parts of copper salt antioxidant were added while stirring at a stirring frequency of 27 Hz to obtain a mixed solution;

[0044] (2) Polymerization: The mixed solution obtained in step (1) is filtered through a filter with a mesh size of 200 meshes through potential difference and pressure difference to remove impurities, and then transported to a refined salt storage tank, and then pumped into a reaction preheater by a reactor supply pump. After preliminary heating in the reaction preheater at 180° C., the mixed solution is pumped into the reactor by a gear pump, and the temperature is raised to 205° C. and the pressure is raised to 1.5 MPa for dehydration for 2 hours, so that the concentration of the mixed solution is 90-95%; the mixed solution is pumped into a flash evaporator by a flash evaporator supply pump and dehydrated at 270° C. and normal pressure for 3 hours to obtain nylon oligomers; the mixed solution is pumped into a prepolymerizer by a potential difference and dehydrated at 255° C. for 3 hours, and then pumped into a postpolymerizer by a postpolymerizer supply pump and dehydrated and polymerized at 255° C. for 2 hours to obtain a polymer in a molten state, and then pumped into a casting head by a melt metering pump for extrusion distribution to form a long carbon chain nylon composite material in the form of a strand belt;

[0045] (3) pelletizing: cooling the long carbon chain nylon composite material in the form of a strand bundle obtained in step (2) with deoxygenated water at 25° C. and then pelletizing to obtain long carbon chain nylon composite material particles;

[0046] (4) Drying: The long carbon chain nylon composite material particles obtained in step (3) are placed in a drying device and dried at 100° C. for 4 hours to obtain a long carbon chain nylon composite material. Figure 2 shown.

[0047] Examples 2-7 and Comparative Examples 1-4 adopt the same continuous synthesis steps as Example 1 to obtain different long carbon chain nylon composite materials.

[0048] The specific formulations of Examples 2-7 and Comparative Examples 1-4 are shown in Table 1:

[0049] Table 1 Formulas of Examples and Comparative Examples

[0050]

[0051]

[0052] Test example

[0053] The performance of the different long carbon chain nylon composite materials obtained in Examples 1-7 and Comparative Examples 1-4 was tested, and the testing method was as follows:

[0054] Tensile properties: Tested in accordance with GB / T 1040-2006 "Determination of tensile properties of plastics", the test temperature is 23°C, and the tensile rate is 50mm / min;

[0055] Simple supported beam notch impact strength: Tested in accordance with GB / T 1043-2008 "Determination of simply supported beam impact properties of plastics", using V-notch specimens, test temperature of 23°C, pendulum energy of 5.5J;

[0056] Thermal conductivity test: Use DRL-Ш thermal conductivity tester (heat flow method) to test the thermal conductivity of the sample in accordance with ASTM E1461-2013 "Standard test method for thermal diffusivity by flash method";

[0057] Surface resistivity test: refer to GBT-1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials" to test the surface resistivity of the sample.

[0058] After testing, the performance test results of the long carbon chain nylon composite materials of the above embodiments and comparative examples are shown in Table 2:

[0059] Table 2 Material performance test results of the embodiments and comparative examples

[0060]

[0061] It can be seen from Table 2 that from Examples 1 to 3, at the same addition amount, the spherical GO / BNNSs prepared at different stripping times have different thermal conductivity effects, and the thermal conductivity effect increases with the increase of the stripping time. This is because the stripping time directly affects the size of the nanosheets. As the stripping time increases, the size of the spherical GO / BNNSs becomes smaller, and the smaller the size, the better the compatibility with nylon salt, and thus the thermal conductivity of the obtained composite material is better.

[0062] It can be seen from Examples 3-6 that with the increase in the amount of spherical GO / BNNSs added, the spherical GO / BNNSs and nylon are in full contact with each other, forming more heat conduction pathways, which significantly improves the thermal conductivity of the nylon composite material. The spherical GO / BNNSs prepared by peeling for 6h have higher thermal conductivity.

[0063] It can be seen from Comparative Examples 3, 4 and Example 6 that GO and BNNSs in GO / BNNSs are tightly bound by π-π bonds, the heat conduction path is more compact and effective, and the thermal conductivity is better. It can be seen from Comparative Example 2 and Example 6 that when the GO / BNNSs stripping time and addition amount are the same, the spherical GO / BNNSs are better than the long carbon chain nylon composite material obtained by the sheet GO / BNNSs. The spherical filler forms an effective interconnected network, and the obtained composite material has a higher thermal conductivity.

[0064] In Example 7, the spherical GO / BNNSs obtained by peeling for 2h and the spherical GO / BNNSs obtained by peeling for 6h were compounded in a 1:1 ratio. When spherical GO / BNNSs of different sizes were compounded, the small-sized spheres filled the gaps between the large-sized spheres and quickly established a heat conduction pathway, showing more excellent thermal conductivity. Compared with Comparative Example 1, the thermal conductivity of the long carbon chain nylon composite material increased from 0.2W / (m·K) to 13.5W / (m·K), and it also had high tensile strength, high impact strength and excellent insulation.

[0065] To further verify the thermal conductivity of the long carbon chain nylon composites prepared from spherical GO / BNNSs, the nylon composites of the spherical GO / BNNSs obtained in Example 6 and the sheet GO / BNNSs obtained in Comparative Example 2 were injection molded into 5 mm thick discs, placed on a heating plate at 52°C, and their surface temperatures were observed by an infrared thermal imager after 60 seconds.

[0066] like Figure 3 As shown, compared with flake GO / BNNSs, the high thermal conductivity nylon composite containing spherical GO / BNNSs exhibits excellent thermal conductivity.

[0067] The present invention is based on the formula of high thermal conductivity long carbon chain nylon composite material. By adjusting the specific process parameters of each step in the continuous production device, each link from raw material feeding to discharging, pelletizing and other links is automated, and a high thermal conductivity long carbon chain nylon composite material is obtained, which significantly improves the production efficiency, and the produced product is more stable than intermittent polymerization.

Claims

1. A high thermal conductivity long carbon chain nylon composite material, characterized in that: The components include the following by mass: Long carbon chain nylon salt: 70-95 parts; Spherical GO / BNNSs: 5-30 parts; Catalyst: 0.01-0.05 parts; Antioxidant: 0.01-0.1 parts.

2. The high thermal conductivity long carbon chain nylon composite material according to claim 1, characterized in that: The preparation method of the spherical GO / BNNSs comprises: adding hydrophilic graphite oxide and hexagonal boron nitride to water, exfoliating for 1 to 7 hours to obtain a GO / BNNSs dispersion, and then spray drying to obtain spherical GO / BNNSs; the spherical GO / BNNSs are compounded by exfoliating spherical GO / BNNSs for 1 to 3 hours and 5 to 7 hours at a mass ratio of 1:1 to 2.

3. The high thermal conductivity long carbon chain nylon composite material according to claim 2, characterized in that: The mass ratio of the hydrophilic graphite oxide, hexagonal boron nitride and water is 5:1-3:

100.

4. The high thermal conductivity long carbon chain nylon composite material according to claim 2, characterized in that: The stripping rotation speed is 1800-2200 rpm.

5. The high thermal conductivity long carbon chain nylon composite material according to claim 2, characterized in that: The spray drying temperature is 170-190° C. and the time is 5-15 minutes.

6. The high thermal conductivity long carbon chain nylon composite material according to claim 1, characterized in that: The long carbon chain nylon salt is prepared from a dibasic acid, a diamine and water; the molar ratio of the dibasic acid, the diamine and water is 1:0.9 to 1.1:25; the dibasic acid is one or more of adipic acid, sebacic acid, undecanedioic acid and dodecanedioic acid; the diamine is decanediamine or dodecanediamine.

7. The high thermal conductivity long carbon chain nylon composite material according to claim 1, characterized in that: The catalyst is one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, sodium phosphite, and sodium hypophosphite.

8. The high thermal conductivity long carbon chain nylon composite material according to claim 1, characterized in that: The antioxidant is one or more of transition metal salts, hindered amines, hindered phenols, phosphites and thiols.

9. The continuous synthesis method of the high thermal conductivity long carbon chain nylon composite material according to claims 1-8, characterized in that: Long carbon chain nylon salt, spherical GO / BNNSs, catalyst and antioxidant are added into the salt-forming tank of the continuous production line, and then a high thermal conductivity long carbon chain nylon composite material is obtained through salt-forming, polymerization, pelletizing and drying.

10. The continuous synthesis method of the high thermal conductivity long carbon chain nylon composite material according to claims 1-8, characterized in that: The method comprises the following steps: (1) Salt formation: Add dibasic acid, diamine and pure water into the salt formation tank in sequence to obtain long carbon chain nylon salt, set the salt formation temperature to 70-80°C, take a sample and test the pH value to be 8.5-9.5, then add spherical GO / BNNSs, catalyst and antioxidant while stirring at a stirring frequency of 20-30 Hz to obtain a mixed solution; (2) Polymerization: The mixed solution obtained in step (1) is filtered through a filter with a mesh size of 180-220 mesh to remove impurities through potential difference and pressure difference, and then transported to a refined salt storage tank, and then pumped into a reaction preheater by a reactor supply pump. After preliminary heating in the reaction preheater at 160-200° C., the mixed solution is pumped into a reactor by a gear pump, and the temperature is raised to 200-210° C. and the pressure is raised to 1-2 MPa for dehydration for 1-3 hours, so that the concentration of the mixed solution is 90-95%; The mixed solution is pumped into the flash evaporator by a flash evaporator supply pump and dehydrated for 2 to 4 hours at 260 to 280° C. and normal pressure to obtain a nylon oligomer; the mixed solution is pumped into the prepolymerizer by a potential difference and dehydrated for 2 to 4 hours at 250 to 260° C., and then pumped into the postpolymerizer by a postpolymerizer supply pump and dehydrated and polymerized for 1 to 3 hours at 250 to 260° C. to obtain a polymer in a molten state; the mixed solution is pumped into the casting head by a melt metering pump for extrusion distribution to form a high thermal conductivity long carbon chain nylon composite material in the form of a strand belt; (3) pelletizing: cooling the high thermal conductivity long carbon chain nylon composite material in the form of a strand bundle obtained in step (2) with deoxygenated water at 23 to 27° C. and then pelletizing to obtain high thermal conductivity long carbon chain nylon composite material particles; (4) Drying: The high thermal conductivity long carbon chain nylon composite material particles obtained in step (3) are placed in a drying device and dried at 90 to 110° C. for 3 to 6 hours to obtain a high thermal conductivity long carbon chain nylon composite material.

Citation Information

Patent Citations

  • Insulating high-strength nano composite material and preparation method thereof

    CN110734642A